The methodical approach to assessing the financial potential of industrial enterprises taking into synergistic approach (Economics and region, 2018)
Imbalance functioning of industries, violations of organizational and economic relations, and the weakening of state influence on the reproductive process of the industrial complex is the result of market reforms and the country's deep crisis that engulfed the Ukrainian industrial complex. These problems lead to the need for such an important analytical work directly as the measurement of the financial capacity of enterprises. Currently, the evaluation of potential growth of the majority of enterprises use only standard methodology for assessing the financial analysis that is based on the calculation of various factors such as financial stability, profitability and business activity. Therefore there is the problem of finding such methods of assessing the financial potential of the company, which will identify the most significant problems (bottlenecks) in the industrial, economic and financial activity, establish their causes, identify ways to increase the positive financial result, which is essential for sustainable development and to increase competitiveness of industrial enterprises. The methodical approach to the measurement of the financial capacity of the industrial enterprise, covering all the basic in-house processes. It is concluded that the proposed approach provides a systematic assessment of industrial enterprises, which will identify strengths and weaknesses and to create on this basis a comprehensive plan for future development.
Keywords: financial capacity; financial capacity assessment methodology; synergetic approach; an industrial enterprise